Asymptomatic bacteriuria in pregnancy - Raguraman, S.; Balagobi, B.; Camilas, J.C. (Sri Lanka Journal of Obstetrics and Gynaecology, 2023)
Asymptomatic bacteriuria (ASB) is diagnosed by the presence of a 10*5 colony-forming units (CFU) in the urine without any urinary symptoms. It commonly occurs in pregnancy with the incidence ranging from 2-10%. It poses a risk of progressing into pyelonephritis in pregnancy. Adverse fetal outcomes include preterm labor, neonatal sepsis, intrauterine growth restriction (IUGR) and neonatal death. Anatomical and physiological changes during pregnancy make pregnant women more vulnerable to ASB and subsequently symptomatic UTI. E coli is the commonest organism involved in ASB, followed by Klebsilla and Enterobactericiae. Evidence suggests that importance of routine screening for ASB in early pregnancy to avoid adverse fetomaternal outcomes. Reduced adverse outcomes were noted with prompt antibiotic treatment for ASB compared to untreated pregnant women with ASB. Urine culture remains as the gold standard method to diagnose ASB in pregnancy. Using urine culture as a routine screening method in Sri Lanka is limited due to financial restrictions.
Keywords: Asymptomatic bacteriuria; Urinary tract infection; Screening; Pregnancy